Maternal and Perinatal Outcome in Adolescent Pregnancies as Compared to Adult Pregnancies - Khaniya, Bishal (Nepal Journal of Health Sciences, 2021)
Introduction: Adolescence is the period between the ages of 10-19 years that encompasses time from onset of puberty to full legal ages (WHO 2002). Objective: The objective of the study was to explore effect of maternal ages on fetomaternal and perinatal outcome. Methods: This is a hospital based retrospective case-control study conducted over 1 year (March 2017 to February 2018) in the department of Obstetrics and Gynaecology in Tribhuvan University Teaching Hospital to study the antenatal complications and perinatal outcome in adolescent pregnant women as compared to pregnant women of age 20-30 years. Results: During this study period, there were 4980 deliveries out of which adolescent pregnancy were 140(2.8%). Anemia was significantly more in teenage group (16.42% vs 8.57%, p=0.047). Incidence of hypertensive disorders was 5.71% and 1.42% (p=0.05) in teenage and adult group. Proportion of babies with intrauterine growth restriction was 5.71% in teenage and 1.42% (p=0.05) in adult group. Low birth weight babies were significantly higher in teenage group than adult group 16.42% vs 8.57% (p=0.047). NNU admission and apgar score were significantly higher in teenage group 5.71% vs 1.42%. Conclusion: Teenage pregnancies are associated with adverse obstetric and perinatal outcome.